First Amendment Equal Protection: On Discretion, Inequality, and Participation - Tokaji, Daniel P. (2003)
The tension between equality and discretion lies at the heart of some of the most vexing questions of constitutional law. The considerable discretion that many official decisionmakers wield raises the spectre that violations of equality norms will sometimes escape detection. This is true in a variety of settings, whether discretion lies over speakers' access to public fora, implementation of the death penalty, or the recounting of votes. Is the First Amendment violated, for example, when a city ordinance gives local officials broad discretion to determine the conditions under which political demonstrations may take place? Is equal protection denied where the absence of uniform standards for vote recounts gives low-level bureaucrats wide latitude in determining which votes to count?6 The subject of this Article is the role of the courts in policing the distorting effects of discretion upon constitutional equality, particularly where rights of political participation are at stake. It uses the term First Amendment Equal Protection to refer to those cases applying an especially searching mode of analysis where the government threatens to undermine equality in the realm of expression. At the core of First Amendment Equal Protection, I argue, is the democratic ideal that all citizens should have an equal opportunity to participate in public discourse. The cases that I include under this rubric exhibit a heightened sensitivity to the threat to equality posed by excessive official discretion. This sensitivity has led to stringent tests designed to smoke out illicit motivations. Among the doctrines developed to cabin discretion in the realm of speech are rules requiring exceptionally clear standards where government requires permission to speak in public places, and liberal rules regarding facial challenges, justiciability, and appellate factfinding. These safeguards against inequality in the realm of speech have for the most part endured, despite the changing makeup of the Court and judicial philosophies of its members